Zadie the sewing fairy - Meadows, Daisy (London : Orchard Books, 2014)
Rainspell Island is hosting an Arts and Crafts Week. Rachel and Kirsty can't wait to try all the different creative activities! But Jack Frost has other plans. He likes making chaos more than making art. The goblins have stolen Zadie the Sewing Fairy's thimble and no one can sew a stitch while it's gone. Kirsty and Rachel must leap into action!"--Page [4] of cover.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Sewing -- Juvenile fiction; Fairies -- Fiction; Magic -- Fiction; Sewing -- Fiction; Fairies; Magic; Sewing; Juvenile works; Fiction